2013
DOI: 10.3389/fncir.2013.00146
|View full text |Cite
|
Sign up to set email alerts
|

Acutely increasing δGABAA receptor activity impairs memory and inhibits synaptic plasticity in the hippocampus

Abstract: Extrasynaptic γ-aminobutyric acid type A (GABAA) receptors that contain the δ subunit (δGABAA receptors) are expressed in several brain regions including the dentate gyrus (DG) and CA1 subfields of the hippocampus. Drugs that increase δGABAA receptor activity have been proposed as treatments for a variety of disorders including insomnia, epilepsy and chronic pain. Also, long-term pretreatment with the δGABAA receptor–preferring agonist 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol (THIP) enhances discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 76 publications
(141 reference statements)
3
27
0
Order By: Relevance
“…This has been shown with a GABA agonist, gaboxadol (Whissell et al, 2013a), at a dose selective for α4βδ GABARs (Brown et al, 2002), as well as for amnestic, sedative drugs such as propofol, isoflurane and benzodiazepines (del Cerro et al, 1992; Nagashima et al, 2005; Saab et al, 2010) although long-term activation of α4βδ GABARs in dentate gyrus improves memory via an effect on neurogenesis (Whissell et al, 2013b). Knock-out of either α4 or δ subunits has also been shown to improve contextual-dependent fear conditioning (Moore et al, 2010; Wiltgen et al, 2005) although sex differences were observed in which trace conditioning or delay conditioning were selectively affected, in female versus male mice, respectively (Moore et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown with a GABA agonist, gaboxadol (Whissell et al, 2013a), at a dose selective for α4βδ GABARs (Brown et al, 2002), as well as for amnestic, sedative drugs such as propofol, isoflurane and benzodiazepines (del Cerro et al, 1992; Nagashima et al, 2005; Saab et al, 2010) although long-term activation of α4βδ GABARs in dentate gyrus improves memory via an effect on neurogenesis (Whissell et al, 2013b). Knock-out of either α4 or δ subunits has also been shown to improve contextual-dependent fear conditioning (Moore et al, 2010; Wiltgen et al, 2005) although sex differences were observed in which trace conditioning or delay conditioning were selectively affected, in female versus male mice, respectively (Moore et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, acute increases in δGABA A receptor activity impair memory and inhibit LTP in the hippocampus [20]. Moreover, the blockade of GABA A receptors facilitates the induction of LTP [21] and rescues propofol-mediated impairment of LTP in the hippocampus [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that reducing GABA inhibition facilitates synaptic plasticity (Paulsen and Moser, 1998; Wigstrom and Gustafsson, 1983), while GABA agonists impair LTP (Whissell et al, 2013): Positive GABA modulators which enhance GABA inhibition, including benzodiazepines and anesthetics, are known to be amnestic in humans (Veselis et al, 2009). These drugs, and others such as alcohol, impair hippocampal synaptic plasticity and spatial learning in rodents (del Cerro et al, 1992; Izumi et al, 2005; Matthews et al, 2002; Nagashima et al, 2005; Saab et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Knock-out of either α4 or δ subunits has also been shown to improve this type of learning (Moore et al, 2010; Wiltgen et al, 2005) although sex differences were observed in which trace conditioning or delay conditioning were selectively affected, in female versus male mice, respectively (Moore et al, 2010). Other studies have shown that acute administration of gaboxadol, to activate δ-containing GABARs, impairs both LTP and spatial learning in the hippocampus (Whissell et al, 2013). …”
Section: Discussionmentioning
confidence: 99%